2017
DOI: 10.1371/journal.pone.0167915
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bartonella Species in Insectivorous Bats, Northern China

Abstract: Bartonella species are emerging human pathogens. Bats are known to carry diverse Bartonella species, some of which are capable of infecting humans. However, as the second largest mammalian group by a number of species, the role of bats as the reservoirs of Bartonella species is not fully explored, in term of their species diversity and worldwide distribution. China, especially Northern China, harbors a number of endemic insectivorous bat species; however, to our knowledge, there are not yet studies about Barto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…Reports of Bartonella spp. infections are known from blood of bats (Judson et al 2015, Han et al 2017, Urushadze et al 2017), from tissues (Bai et al 2017, Stuckey et al 2017) and from their associated ectoparasites (Morse et al 2012, Davoust et al 2016, Sándor et al 2018, Hornok et al 2019). In our study this pathogen group was found in low proportions, in two samples (2 out of 10, 20%), but the PCR targeting the ITS gene of Bartonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of Bartonella spp. infections are known from blood of bats (Judson et al 2015, Han et al 2017, Urushadze et al 2017), from tissues (Bai et al 2017, Stuckey et al 2017) and from their associated ectoparasites (Morse et al 2012, Davoust et al 2016, Sándor et al 2018, Hornok et al 2019). In our study this pathogen group was found in low proportions, in two samples (2 out of 10, 20%), but the PCR targeting the ITS gene of Bartonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, 35 species of Bartonella have been identified (http://www.bacterio.net/index .html) and have international standing in nomenclature, and other species have been proposed, several of which are classified as "Candidatus" species (80). New species of Bartonella continue to be discovered, but frequently only partial genetic data obtained by molecular analysis are available (81)(82)(83). B. rochalimae was reported in 2007 to have caused an Oroya fever-like disease in a traveler returning from Peru (57), and a retrospective study also identified this species in the blood of a Peruvian patient with Carrion's disease (84).…”
Section: Bartonellaceaementioning
confidence: 99%
“…Details regarding anesthetization of bats and tissue sampling were described previously ( 5 ). We collected the kidneys, storing them at −80°C until analysis.…”
Section: The Studymentioning
confidence: 99%